"Golden" Cascade Cyclization to Benzo[c]‐Phenanthridines. Issue 59 (12th September 2021) - Hendrich, Christoph M.; Senn, Sebastian; Haas, Lea; Hoffmann, Marvin T.; Zschieschang, Ute; Greiner, Luca C.; Rominger, Frank; Rudolph, Matthias; Klauk, Hagen; Dreuw, Andreas; Hashmi, A. Stephen K.
Abstract: Herein, we describe a gold‐catalyzed cascade cyclization of Boc‐protected benzylamines bearing two tethered alkyne moieties in a domino reaction initiated by a 6‐ endo‐dig cyclization. The reaction was screened intensively, and the scope was explored, resulting in nine new Boc‐protected dihydrobenzo[ c ]phenanthridines with yields of up to 98 %; even a π‐extension and two bidirectional approaches were successful. Furthermore, thermal cleavage of the Boc group and subsequent oxidation gave substituted benzo[ c ]phenanthridines in up to quantitative yields. Two bidirectional approaches under the optimized conditions were successful, and the resulting π‐extended molecules were tested as organic semiconductors in organic thin‐film transistors. Abstract : Suitable substitution : The synthesis of highly substituted six‐membered N‐heterocycles using gold catalysis is reported. The applied cascade reaction using different substituted alkyne systems as starting materials furnished the corresponding benzo[ c ]phenanthridines in very high overall yields. In addition, two π‐extended molecules were studied as organic semiconductors in organic thin‐film transistors.